A Non-Profit Approach to Address Foreign Dependence of Generic Drugs. Issue 1 (2021) - Liljenquist, Dan; Bai, Ge; Sarpatwari, Ameet; Anderson, Gerard F.
Abstract: The COVID-19 pandemic has revealed the vulnerability of the US generic drug supply chain to foreign production. Many policies have been proposed to mitigate this vulnerability. In this article, we argue that nonprofit drug manufacturers have the potential to make important contributions.